Containerboom: Chance für den KV. - Jung, Christian (Deutscher Verkehrs-Verl., 2006)
Der Frachtumschlag in den deutschen Seehäfen hat einen neuen Höchststand erreicht. Nach Angaben des Statistischen Bundesamts wurden im vergangenen Jahr fast 285 Mio. t an Nord- und Ostsee umgeschlagen, 4,8 % mehr als 2004. Seit 1992, als zum ersten Mal gesamtdeutsche Zahlen veröffentlicht wurden, hat sich das Volumen damit um fast 56 % erhöht. Doch je mehr Fracht in den deutschen Seehäfen abgefertigt wird, umso leistungsfähiger müssen auch die Vor- und Nachlaufwege sein. difu

Expansion of regional airports: misallocation of resources. The planned expansion of most regional airports in Germany is a waste of scarce public funds. Only a few regional airports can be operated economically, Most of them offer no potential to ease the congestion at larger airports, do not have critical mass, cannibalise one another and compete with each other for subsidies. Moreover, they are often dependent on a single low-cost carrier. The projects are mainly prestige objects for regional politicians. The expansion of unprofitable, publicly financed regional airports leads to competitive distortions, Germany already has enough airports and only a few of them are struggling with capacity bottlenecks. Sensible economic governance can help redress these ills. For one thing, shifting responsibility for decision-making to the federal level will overcome the risk of egotistic considerations at the regional level. For another, privatisation will solve the efficiency problems. Possible losses would not land in the taxpayer's lap. difu
Keywords: Öffentlicher Verkehr; Seehafen; Hafen; Verkehrsstatistik; Container; Schienengüterverkehr; Verkehrsteilung; Gebrochener Verkehr; Containerhafen; Transportaufkommen; Wirtschaftsstatistik; Frachtverkehr